Teaching nation-building and nationalism: a critical perspective of Turkish academia (Journal of Applied Learning and Teaching, 2022)
The process of nation-building can be seen as a never-ending attempt for a considerable number of nation-states. Education has been one of the primary tools in this process. It can be argued that nation-building policies should be seen as aspects of an attempt rather than a project that can be realized successfully in all terms. Following this argument, this study has two main objectives: to draw a detailed literature review addressing the dynamics, actors and stages of the nation-building process and nationalism and to critically analyze how Turkish academia has dealt with nationalism education. This study will proceed via the following sections: Firstly, the main theoretical discussions concerning nationalism will be covered. In this regard, ethnic/civic nationalism and other types of nationalism, including the concept of “banal nationalism” coined by Michael Billig (1995) will be under scrutiny. Secondly, the state-formation process from a cultural viewpoint will be analyzed. In this part, the works of thinkers such as Pierre Bourdieu, Michel Foucault and Antonio Gramsci will be referred to. Next, ‘the nation-building process as a never-ending attempt’ will be addressed. Finally, the teaching of nationalism in Turkish academia will be discussed from a historical viewpoint.